Development of the Si PaPa Gasi Module (First Aid for Preeclampsia/Eclampsia) with a Family Approach in the Archipelago Region - Haryadi, Haryadi; Aminin, Fidyah; Damayani, Ayi Diah; Jannah, Rawdatul (Jurnal Kesehatan, 2024)
Maternal deaths in the Riau Islands Province in 2020 are still dominated by direct causes, namely hypertension in pregnancy (around 39%), known as preeclampsia and eclampsia. The Community Health Center also does not have a particular module regarding first aid in emergencies if preeclampsia or eclampsia occurs. This research aims to determine the effectiveness of the Si PaPa Gasi Module (First Aid in Preeclampsia/Eclampsia emergencies) with a family approach in island areas. The research design is a quasi-experiment with a pre-posttest and control group design. The population is all pregnant women in the Berakit Health Center working area. The total sample was 47 in the intervention group and 47 in the control group. The research instrument is a questionnaire. Statistical analysis uses the computer program by looking at the increase in the average (mean) and the influence of the independent variable on the dependent variable using the t-test. The results of the Si PaPa Gasi module research were Si PaPa Gasi module could increase knowledge regarding First Aid for Preeclampsia/Eclampsia Emergencies and increase the attitudes and motivation of pregnant women to perform First Aid for Preeclampsia/Eclampsia Emergencies. Health facilities can use the PaPa Gasi module as a health education media in efforts to prevent preeclampsia and eclampsia.